Vulneración del principio establecido en el art. 229 de la constitución de la república del ecuador, referente a la irrenunciabilidad del derecho de los servidores públicos a la estabilidad laboral, por la figura jurídica del contrato de servicios ocasionales previsto en el art. 58 de la ley orgánica del servicio público y su reglamento general - Paute Lalangui, Carlos Edilverto (2015)
This thesis entitled; "Violation of the principle laid down in Art. 229 of the Constitution of the Republic of Ecuador concerning the indispensability of the right of public servants to job security, the legal concept of occasional services contract provided for in Art. 58 the Organic Law of the Public Service and its General Regulations ", is a legal problem because many public institutions hire staff through the type of contract for occasional services, allowing work in the public institution for many years, due to the urgency of the replacement institution or staff; this has been going on since 58 of the Organic Law of the Public Service authorizes the signing of contracts of occasional services is authorized by the appointing authority, to meet institutional needs. The hiring of casual staff may not exceed 20% of the total staff of the contracting entity, such contracts may not exceed twelve months or until end of the fiscal year. The law exempts from this percentage to those newly created institutions to be incorporated personnel under this mode, until the corresponding selection competitions are conducted merits and opposition, in the relevant part of this article points out that by its very nature, this type of contracts does not create stability; this legal provision creates rights violations and legal contradiction because when analyzing the Art. 229 of the Constitution are the rights of public servants are waived. The law regulates the admission, promotion, promotion, incentives, disciplinary regime, stability, system of remuneration and termination of appointment of its servers. From the aforementioned legal inconsistencies exist to meet in a Constitutional State of Rights and constitutional supremacy it must be fulfilled so mandated by the Constitution to be supreme law that prevails over the Law on Public Service, being necessary to propose amendments to this law which violates the irrevocability Rights of public servants and the right to stability. The development of literature and the results of the survey and interviews allowed me to get criteria, with clear and precise grounds of well known literature, which contributed to the verification of objectives, and the testing of the hypothesis, allowing support changes proposed to the Organic Law of the Public Service. The content of this thesis is the result of an arduous legal research of the author in the scientific, legal, social and methodological level, which deals with theories and knowledge obtained through techniques